Deconstructing who you play: character choice in online gaming - Hodges, Duncan; Buckley, Oliver (Elsevier, 2018)
The major growth in gaming over the last five to ten years has been through the expansion in online gaming, with the most frequent gamers now playing more games online than with others in person. The increase in cooperative multiplayer online gaming, where players who do not know each other come together in teams to achieve a common goal, leads to interesting social situations. The research in this paper is focussed on the online multiplayer game Overwatch, in this game playable characters are grouped into a number of classes and characters within these classes. A player chooses the character at the start of a given round, and whilst they can change the character during the game round this is generally undesirable. In this research we were interested in how players go about selecting a character for a given round of the game, this is a complex interaction where a player has to balance between personal character preference (either a character they enjoy playing or is well-mapped to their playstyle and skill) and ensuring a team has a balance of player classes. The interaction is complicated by the online nature meaning it is difficult to reward a team-mate for selecting a character they may not wish to play or playing a character which may mean they will perform poorly but the team will win. We recruited over 1000 Overwatch players and surveyed them on how they make their character choices within the game, they were also asked to complete various psychometric tests. We found that a gamers player ‘type’ (i.e. Killer, Achiever, Explorer or Socialiser) was defined by their agreeableness and their gender. We also found that player’s choice of character class was related to their level of agreeableness and extroversion modulated by the player’s gender. We also found that those who rate highly in conscientiousness and agreeableness and are socialisers or achievers were more likely to choose a character in order to achieve a balanced team rather than personal preference. The research is unique in the scale and number of respondents, it also addresses a problem in co-operative gaming where players must negotiate the composition of a team. This negotiation is often performed without any background knowledge of other player’s skill levels, this is the first study at this scale considering this within the context of co-operative online gaming.
Keywords: Online gaming; Personality; Character choice; Overwatch